1992
DOI: 10.1288/00005537-199211000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular dysphonia: A profile of 40 cases

Abstract: Ventricular dysphonia is a poorly understood disorder involving ventricular fold participation during phonation. A population of ventricular dysphonia patients was evaluated using phonatory function studies such as laryngovideostroboscopy, advanced acoustic analysis, and electroglottography to identify shared epidemiologic characteristics and to discuss possible neuromuscular mechanisms and causes. Forty patients with ventricular dysphonia were studied and epidemiologic, acoustic, and histologic data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 11 publications
1
37
0
1
Order By: Relevance
“…The basic paradigm that evaluates laryngeal hyperfunction is to look for compression of the supraglottic structures during phonation [29]. This supraglottic activity may be separated into two components: (1) A-P supraglottic activity and (2) medial supraglottic activity [30,31,32]. In the present study most of the participants from the experimental group not only demonstrated laryngeal supraglottic activity during singing, but 14 of them (67%) also presented with some slight degree of laryngeal supraglottic activity during speaking voice tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The basic paradigm that evaluates laryngeal hyperfunction is to look for compression of the supraglottic structures during phonation [29]. This supraglottic activity may be separated into two components: (1) A-P supraglottic activity and (2) medial supraglottic activity [30,31,32]. In the present study most of the participants from the experimental group not only demonstrated laryngeal supraglottic activity during singing, but 14 of them (67%) also presented with some slight degree of laryngeal supraglottic activity during speaking voice tasks.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed information on dynamic characteristics of the other laryngeal structures, like, e.g., the ventricular folds, could also be helpful since these structures contribute to phonation in certain singing styles ͑Fuks et Södersten, 1999͒ or in patients with voice disorders ͑Kruse, 1981;von Doersten et al, 1992;Schutte et al, 1998;Š vec et al, 1997. For a more extensive analysis, however, it is desirable to employ automated or semi-automated image detection ͑Wittenberg, 1997͑Wittenberg, , 1998Saadah et al, 1998;Larsson et al, 1999͒ instead of manual analysis of the images which is exceedingly time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Their physical properties ͑high viscosity and low stiffness͒ are different from those of biomechanical oscillators such as the vocal folds ͑Haji et al, 1992͒. Yet, their vibration has been observed during specific vocal gestures: Asian throat singing ͑Fuks et Lindestad et al, 2001;Sakakibara et al, 2001, 2004͒, Mediterranean traditional polyphony ͑Henrich et al, 2006͒, rock singing ͑Zang-ger Borch et al, 2004͒, pathological phonation ͑Lindestad et al, 2004Nasri et al, 1996;Von Doersten et al, 1992͒. Several vibratory gestures can be distinguished: periodic or aperiodic, in phase or not with the vocal fold vibration, with or without ventricular contact. In this study, we focus on a particular type of ventricular fold vibratory movement, referred to as vocal-ventricular phonation mode by Fuks et al ͑1998͒.…”
Section: Introductionmentioning
confidence: 99%